A prevalence study into use and management of peripheral intravenous catheters - Daud, Azlina; Rahman, Hazimah (Intenational Islamic University Malaysia, 2016)
INTRODUCTION: There are over half of patients admitted to the hospital required peripheral intravascular cannula (PIVC) inserted. However, there is no data reported on the use of PIVC in Malaysia. OBJECTIVES: To determine the prevalence of PIVCs use and management of PIVC. METHODS: An observational study was conducted on patients who had PIVC in medical, surgical, obstetric and orthopedic ward in Hospital Tunku Ampuan Afzan, Kuantan, Malaysia. RESULTS: Over 2 months, the total admission for 4 wards was 1466 and out of this total admission, 490 patients were recruited. Reasons for PIVC insertion were for IV fluids (62.4%) and for medication administration (31.8%). Most of the PIVC inserted in the general ward (91.8%) followed by from emergency department. The PIVC insertion was done by the doctor (84.5%). All patients used same brand of cannula which is Vasofix Branulle and used transparent polyurethane dressing. There was 28 (5.7%) patients have sign of thrombophlebitis. Chi square showed that there was significant association between day of PIVC insertion with thrombophlebitis (p=0.006). CONCLUSIONS: In conclusion, the study processes resulted in a small proportion (33.4%) of patients with PIVC with the total number of admission to the 4 wards and 5.7% patients have sign of thrombophlebitis.